The Impact of Fiscal Sovereignty in the Field of Real Estate Tax on Municipal Revenues - Świerczek-Dutka, Patrycja (Wpływ władztwa podatkowego w zakresie podatku od nieruchomości na dochody gmin, 2024)
Aim: The aim of the article was to assess the significance of the fiscal sovereignty granted to municipalities in Poland in the real estate tax from the perspective of its impact on their revenues. The study determined the scale and nature of the use of fiscal sovereignty instruments by various types of municipalities and to analyse the financial impact of these actions. Methodology: The research encompassed all municipalities in Poland (including cities with county rights as well as urban, rural, and urban-rural municipalities), utilising data provided by the Ministry of Finance for the years 2018-2023. Empirical research methods such as observation, comparison, and measurement were employed, along with descriptive statistics techniques. Findings: The analysis indicated that from 2018 to 2023 the exercise of fiscal sovereignty by municipalities resulted in a total revenue decrease of PLN 20.2 billion (13% of total real estate tax revenue during this period). This confirms the significant impact of utilising fiscal sovereignty instruments on municipal revenues. Notable differences were observed among various types of municipalities, with rural municipalities showing a greater propensity to apply tax preferences. The primary instrument utilised in this regard was the reduction of upper tax rates. Implications: The research findings indicate a need for further, in-depth analysis of the long-term effects of exercising fiscal sovereignty, particularly in the context of local development and municipal competitiveness. Furthermore, they provide valuable information for policymakers and tax authorities, suggesting the potential necessity for modifying current regulations to optimise the municipal revenue system, considering the diverse needs and capabilities of different types of local government units. Originality/value: This study makes a significant contribution through its comprehensive analysis of the effects of fiscal sovereignty application on a national scale, identification of differences in tax strategies among various types of municipalities, and provision of current quantitative data on the scale and nature of the utilisation of specific instruments. Consequently, the research findings can serve as a foundation for further analyses and support in shaping tax policy at both local and national levels.
Financial Sciences. Nauki o Finansach, 2024, vol. 29, no. 1, s. 74-85
Keywords: local taxes; real estate tax; tax system; fiscal sovereignty; local government entities; podatki lokalne; podatek od nieruchomości; system podatkowy; władztwo podatkowe; jednostki samorządu terytorialnego